EDUCATION OF ENTREPRENEURSHIP BASED ON ENTREPRENEURSHIP PROGRAM IN MIDDLE VOCATIONAL SCHOOL (SMKN) 3 BANDUNG - Mas'ud, M. (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2018)
The purpose of this study is to describe the model of implementing entrepreneurship programs in developing entrepreneurial behavior, finding obstacles in managing and developing programs and products, and finding the results of the application of the program to the behavior of students at SMKN 3 Bandung. The research approach uses descriptive qualitative analysis. Data collection techniques using observation, interviews, and documentation. The Entrepreneurship Program at SMKN 3 Bandung in developing entrepreneurial behavior of students is categorized as a partnership program. This is because the entrepreneurship program collaborates with several parties namely the Government of West Java in providing aid funds, as well as coffee observers to help students in producing coffee. In addition, the program is also categorized as a participatory program, because this program involves the school community in its implementation including the principal, students, teachers, and other staff members.